Obrazy stalinizmu w twardym jądrze i na peryferiach. Kłopoty ze Sceną Faktu TVP (2006–2010) - Szpulak, Andrzej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The text refers to the part of the performances of TVP’s Fact Stage (2006–2010), devoted to the Stalinist period, as well as to its journalistic and scholarly reception. In no small part, it is a polemic with the position and reasoning expressed in Mariusz Mazur’s article TV Theater: Fact Stage – a specific vision of history. On such historical politics polemically. The author points to the need to interpret the phenomenon of Fact Stage as it really was, to understand its genesis, social conditions and cultural context. However, he rejects the method of contrasting the works in question with the abstract and normative postulates formulated by Mazur. Finally, the article points to the religious (morality play and passion play) sources of the conception of Fact Stage performances.